If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = 5u + -7 Reorder the terms: -2 = -7 + 5u Solving -2 = -7 + 5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-5u' to each side of the equation. -2 + -5u = -7 + 5u + -5u Combine like terms: 5u + -5u = 0 -2 + -5u = -7 + 0 -2 + -5u = -7 Add '2' to each side of the equation. -2 + 2 + -5u = -7 + 2 Combine like terms: -2 + 2 = 0 0 + -5u = -7 + 2 -5u = -7 + 2 Combine like terms: -7 + 2 = -5 -5u = -5 Divide each side by '-5'. u = 1 Simplifying u = 1
| 4(2b+5)=52 | | 1/6x72 | | 2x+80= | | 5x-2y+5x-2y=20 | | n-14+8n= | | -19(13-17x)= | | 8x+12+9x= | | 5m(2n-7)= | | (2x+20)+(6x+40)=180 | | -7(a+7)=-5(4a+6)-6a | | 12+3(4x-6y)-8y= | | 0.50x+0.6=0.3x-1.5 | | 5x^3+14x^2+8x=0 | | (x-(4+3i))(x-(4-3i))=0 | | x^2=-4x+400 | | 3=m/6 | | 3x^4-1=0 | | h=-16t^224*t-3 | | a+2.75+9.35+(2a+2.75+9.35)*0.0715=261.76 | | 2u-4u=-13+11 | | 6(2y+5)-2y+10= | | a+3+9.35+(2a+3+9.35)*0.0715=261.76 | | 3(x-4)=2-2(6-x) | | u^2-10u-9=0 | | -2(m-4)=7m+4(2+7m) | | a+3.25+9.35+(2a+3.25+9.35)*0.0715=261.76 | | 6z^4-11z^2+3=0 | | 0=16x^2-24x+9 | | 12x+17+15x=180 | | 6(x-4)=3x-60 | | 9(42)-9(4)=9(30)+9 | | -5x-8x+34=5x+26 |